Intraoperative vs. Postoperative Side-Effects-Thresholds During Pallidal and Thalamic DBS - Geraedts, Victor J.; van Ham, Rogier A. P.; van Hilten, Jacobus J.; Mosch, Arne; Hoffmann, Carel F. E.; van der Gaag, Niels A.; Contarino, Maria Fiorella (Frontiers in Neurology, 2021)
BACKGROUND It is currently unknown whether results from intraoperative test stimulation during awake pallidal (GPi) or thalamic (Vim) Deep Brain Stimulation (DBS) are comparable to the results generated by chronic stimulation through the definitive lead. OBJECTIVE To determine whether side effects thresholds from intraoperative test stimulation are indicative of postoperative stimulation findings. METHODS Records of consecutive patients who received GPi or Vim DBS were analyzed. Thresholds for the induction of either capsular or non-capsular side-effects were compared at matched depths and at group-level. RESULTS Records of fifty-two patients were analyzed (20 GPis, 75 Vims). The induction of side-effects was not significantly different between intraoperative and postoperative assessments at matched depths, although a large variability was observed (capsular: GPi DBS: p=0.79; Vim DBS: p=0.68); non-capsular: GPi DBS: p=0.20; Vim DBS: p=0.35.) Linear mixed effect models revealed no differences between intraoperative and postoperative assessments, although the Vim had significantly lower thresholds (capsular side-effects p=0.01, non-capsular side-effects p<0.01). Unpaired survival analyses demonstrated lower intraoperative than postoperative thresholds for capsular side-effects in GPi DBS patients (p=0.01), and higher intraoperative thresholds for non-capsular side-effects in Vim DBS patients (p=0.01). CONCLUSION There were no significant differences between intraoperative and postoperative assessments of GPi and Vim DBS, although thresholds cannot be directly extrapolated at an individual level due to high variability.